Relasi Gender Dalam Islam - Nur Kholis (Journal on Education, 2021)
The differences between men and women still have problematic sides, both in terms of the substance of events and the roles they play in society. The biological anatomical differences between the two are quite clear. However, the effects arising from these differences raise debate, because it turns out that differences in biological sex (sex) have given birth to a set of cultural concepts. This cultural interpretation of gender differences is called gender. Biological differences between men and women have implementative value in cultural life. This fact will be very interesting if it is connected with the Qur'an as the main source of Islamic teachings. The Al-Qur'an is very wise in talking about gender issues by prioritizing the principles of justice, equality and partnership. Nor does the Qur'an deny that there is a difference (distinction) between men and women, but this difference is not a distinction (discrimination) that benefits one party and harms the other.The principles that the Qur'an brings regarding gender have been given various understandings by interpretation scholars and fiqh scholars. As a result, the ideal relationship between men and women as creatures of Allah SWT has occurred at a certain level of distortion, in which one party becomes superior to the other.